Pengaruh Pengelolaan Sarana Prasarana dan Pemahaman Teori Menjahit Terhadap Kualitas Pembelajaran Praktikum pada Jurusan Tata Busana di SMK Negeri 1 Sangatta Utara - Sulistiani Sulistiani; Eko Nursalim; Muh Ibnu Faruk Fauzi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to determine the extent of the influence of infrastructure management and understanding of sewing theory on the quality of practicum learning in the Fashion Department at SMK Negeri 1 Sangatta Utara. This study uses a quantitative approach with data collection methods through questionnaires, observation, and documentation. The research sample amounted to 107 students from a total population of 143 students in classes X, XI, and XII. The results of multiple linear regression analysis show that the management of infrastructure facilities has an influence of 16.26%, while the understanding of sewing theory has a greater influence, namely 71.53% on the quality of practicum learning. Simultaneously, the two variables contributed 87.9%, while 12.1% was influenced by other factors not studied. This finding confirms that the understanding of sewing theory has a more dominant influence than the management of infrastructure facilities in improving the quality of practicum learning in the Cosmetology department at the SMK.